ANALISIS EKSPOR PT BINA MITRA MAKMUR - Aditia Ningtiyas; Chania Cyrda Claudia; Easter Victoria; Helena Milli (AIBPM Publisher, 2018)
This study aims to analyze a product in a company in Indonesia, so that it can be exported to other countries and can add value to Indonesian products. PT Bina Mitra Makmur is a company originating from Jambi Indonesia. The PT produces palm oil. Providing several scales to products, markets, operations and company finances by groups. Is the company eligible to export. The type of payment made by PT Bina Mitra Makmur uses the type of payment of Letter of Credits (L / C), is an institution in the form of collateral issued by the bank at the request of the customer (aplicant) to pay a sum of money to the L / C recipient for submitting a set of documents according to the terms and conditions requested in the L / C. analyze palm oil crude products that can be exported to China, because China is the country with the most population and also the largest importer of oil. Human resources that will be needed in